A Quantitative Histologic Analysis of Oogenesis in the Flatfish Species Pleuronectes platessa as a Tool for Fisheries Management - Carine Sauger; Jérôme Quinquis; Clothilde Berthelin; Mélanie Lepoittevin; Nicolas Elie; Laurent Dubroca; Kristell Kellner (Animals, 2023)
The following paper gives a detailed description of the oogenesis cycle for the European Plaice (Pleuronectes platessa), from oogonia to post-ovulatory follicle, including ovarian follicle and zona pellucida sizes. Noteworthy particularities were the difficulty in identifying cortical alveoli due to their very small size. Quantitative histology (stereology) on histological slides was used to determine a first size at maturity for females from the English Channel, which was found to be smaller compared to the literature (19 cm). Stereology also determined a first spawning event starting in January, with a peak in February and ongoing until March. Moreover, the use of stereology showed misclassifications for individuals categorized into a maturity phase using a macroscopic visual method. Misclassifications were found with individuals that had spawned (D) but were put under the immature (A) phase, and individuals in development (B) classified under D.